Infertility Insurance Mandates and Fertility - Schmidt, Lucie (American Economic Review, 2005)
Infertility is considered by the medical community to be a disease of the reproductive system. It currently affects over 6 million individuals, and one in ten couples cannot conceive without medical assistance. The psychological effects of infertility have been compared to the effects of other diseases such as cancer and heart disease (e.g., Anne T. Fidler and Judith Bernstein, 1999), and the financial costs of treatment can be quite large. However, only 25 percent of all health-plan sponsors provide coverage for infertility services. In response to a perceived need for coverage, legislation was introduced at the federal level in 2003 that would require health plans to provide infertility benefits. As the fraction of the population affected by infertility continues to rise, there are likely to be continued efforts to mandate coverage. Understanding the costs and benefits of these policies thus becomes increasingly important. The first component of a full analysis is to determine whether these mandates will actually have an effect on fertility. By reducing the price of infertility treatment, one might expect to see an increase in utilization of treatments. This could be true if the mandate expands access to individuals who previously could not afford treatment, or if individuals who were previously receiving treatment now choose to consume higher quantities (or a higher quality) of treatment. However, it is also possible that these mandates have no effect on access or on treatment consumed but simply provide windfall gains to those individuals who would have purchased treatment in the absence of insurance coverage. Finally, mandates may also have dynamic effects on the timing of births. Individuals could seek treatment earlier, which is beneficial from a medical perspective. Alternatively, individuals could further delay childbearing, with the knowledge that they will ultimately be covered. In this paper, I ask the first-order question of whether the mandated insurance coverage of infertility treatment has affected birth rates. As of 2003, 15 states have enacted some form of infertility insurance mandate. Using a differencein-differences approach, I exploit variation in the enactment of mandates both across states and over time and identify control groups that should not have been affected by infertility coverage. My results suggest that the mandates increase firstbirth rates for women over age 35 by 32 percent.